A fuzzy inference system approach for habitat suitability index modeling: A case study of Bachman’s sparrow - Cassio Auguto Ussi Monti; Casey Eugene Phillips; Joseph Peter Roise; John Paul McTague; Christopher Moorman; Rachel Cook (Ecological Modelling, 2026)

Improving payment for essential services – A field experiment in Nairobi, Kenya - David Fuente; Mbutu Mwaura; Josiah Gitu; Richard Mulwa; Joseph Cook (Utilities Policy, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Translating community perceptions and concerns into planning: climate change adaptation in Hooper Bay, Alaska - Joseph T. Molina; Agatha A. Napoleon; Estelle Angutekaraq Thomson; Colleen Timmer; Andre Simon; Agulria Smart; Billy Tinker-Smith; Nicole Schmitt; Chelsey Cook (Regional Environmental Change, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Bipolar volcanic ice-core synchronization of the entire last glacial period - Anders Svensson; Guido Vettoretti; Jia-mei Lin; Giulia Sinnl; Dorthe Dahl-Jensen; Jørgen Peder Steffensen; Sune Olander Rasmussen; Bo Vinther; Christine Hvidberg; Helle Astrid Kjær; Vasileios Gkinis; Eliza Cook; et al. (Quaternary Science Reviews, 2026)

A Dominant Founder Lineage Has Possible Fitness Costs for the Endangered Mexican Grey Wolf - Yeraldi Loera; Manisha Khakoo; Emily Krueckeberg; Ingrid G. Nilsson; Zehao Wu; Maggie Dwire; Jennifer Adams; Lisette Waits; John K. Oakleaf; Mariel L. Campbell; Jonathan L. Dunnum; Joseph A. Cook; et al. (Molecular Ecology, 2026)
The Mexican grey wolf ( Canis lupus baileyi ) is an endangered and genetically distinct subspecies of grey wolf adapted to the warm climates of the southwestern United States and Mexico. Following centuries of eradication efforts, Mexican grey wolves were protected under the Endangered Species Act in 1976, prompting an international ex situ breeding program to preserve their genetic legacy. Seven remnant wolves founded the three distinct lineages of this program: McBride, Ghost Ranch, and Aragón. However, concerns of rising inbreeding levels motivated the implementation of inter‐lineage pairings to decelerate genetic erosion. To evaluate the genetic health of the ex situ managed population, we analysed genome‐wide variation across several generations of breeding wolves and their descendants ( n = 179). Despite ongoing conservation interventions, we found a sharp decline in effective population size over the past 50 generations. However, estimates of inbreeding diminished over time following the inter‐lineage pairings, reflecting efficient pedigree management or potential fitness costs of inbreeding depression, as higher levels of inbreeding and autozygosity were associated with reduced lifespan and reproductive performance. Increasing contributions of Ghost Ranch and Aragón ancestry also aided in reducing levels of inbreeding observed in the more genetically distinct McBride lineage. These findings highlight the challenges of maintaining genetic diversity in bottlenecked populations, reveal fine‐scale patterns of inbreeding within the pedigree and underscore the urgent need to preserve genetic contributions from all founder lineages. Genomic insights from this study can guide breeding strategies to reduce kinship, balance ancestry and mitigate inbreeding depression, safeguarding the evolutionary legacy and the long‐term persistence of the Mexican grey wolf.

Associations of endocrine disrupting chemical biomarkers and their mixture with vitamin D biomarker concentrations in childhood: The HOME Study - Katherine M. Marquess; Jordan R. Kuiper; Taylor M. Etzel; Bruce P. Lanphear; Andrew N. Hoofnagle; Antonia M. Calafat; Julianne Cook Botelho; Maria Ospina; Andreas Sjodin; Lesliam Quirós-Alcalá; Kim M. Cecil; Aimin Chen; et al. (Environmental Research, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Time since HIV diagnosis is linked to amnestic mild cognitive impairment (MCI) in older adults with HIV - Jason S. DeFelice; Mark K. Britton; Yancheng Li; Eric C. Porges; Gladys E. Ibañez; Charurut Somboonwit; Robert L. Cook; Ronald A. Cohen; Joseph M. Gullett (Journal of NeuroVirology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Ecosystem-wide PFAS characterization and environmental behavior at a heavily contaminated desert oasis in the southwestern U.S. - Jean-Luc E. Cartron; Chauncey R. Gadek; Jonathan L. Dunnum; Christopher C. Witt; Mariel L. Campbell; Samuel J. Romero; Andrew B. Johnson; Julie Kutz; Christopher Wolf; Sarah J. Choyke; Joseph A. Cook (Environmental Research, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Correction to: Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2025)

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Remote sensing of ice albedo using harmonized Landsat and Sentinel 2 datasets: validation - Shunan Feng; Joseph Mitchell Cook; Yukihiko Onuma; Kathrin Naegeli; Wenxia Tan; Alexandre Magno Anesio; Liane G. Benning; Martyn Tranter (International Journal of Remote Sensing, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Uncovering further diversity of Ochoterenatrema Caballero, 1943 (Digenea: Lecithodendriidae) in South American bats - Vasyl V. Tkach; Roxanne Gasperetti; Thayane F. Fernandes; Carlos A. Carrión-Bonilla; Joseph A. Cook; Tyler J. Achatz (Systematic Parasitology, 2024)
Ochoterenatrema Caballero, 1943 is a genus of lecithodendriid digeneans that prior to this study included 8 species parasitic in bats in the Western Hemisphere. Species of Ochoterenatrema possess a unique morphological feature in form of the pseudogonotyl on the sinistral side of the ventral sucker. In this study, we describe 2 new species of Ochoterenatrema from bats in Ecuador. The new species are readily differentiated from their congeners by a combination of morphological characters, including the distribution of vitelline follicles, length of oesophagus, sucker ratio and the body shape, among other features. We have generated partial nuclear 28S rDNA and mitochondrial cox 1 gene DNA sequences from both new species. The newly obtained sequences were used to differentiate among species and study the phylogenetic interrelationships among Ochoterenatrema spp. The internal topology of the clade was weakly supported, although the cox 1 tree was much better resolved than the 28S tree. Comparison of sequences revealed 0–1.2% interspecific divergence in 28S and 3.3–20.5% interspecific divergence in cox 1 among Ochoterenatrema spp. The new findings demonstrate that bats in South America likely harbor multiple additional undescribed species of Ochoterenatrema . More extensive sampling from broader geographic and host ranges, especially in North America, should allow for a better understanding of the evolution of host associations and morphological traits of this lineage of lecithodendriid digeneans.

Is EGD Needed in all Patients after Suicidal or Exploratory Caustic Ingestions? - Michael Levine; Yaron Finkelstein; William J. Trautman; Dazhe Cao; Evan Schwarz; Ari Filip; Leanne Cook; Sameer Arbussattar Pathan; Cherie Obilom; Jim Liu; Joseph Yanta; Neta Cohen; et al. (Journal of Medical Toxicology, 2024)

Extraordinary levels of per- and polyfluoroalkyl substances (PFAS) in vertebrate animals at a New Mexico desert oasis: Multiple pathways for wildlife and human exposure - Christopher C. Witt; Chauncey R. Gadek; Jean-Luc E. Cartron; Michael J. Andersen; Mariel L. Campbell; Marialejandra Castro-Farías; Ethan F. Gyllenhaal; Andrew B. Johnson; Jason L. Malaney; Kyana N. Montoya; Andrew Patterson; Nicholas T. Vinciguerra; et al. (Environmental Research, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Mid-to Late Holocene East Antarctic ice-core tephrochronology: Implications for reconstructing volcanic eruptions and assessing their climatic impacts over the last 5,500 years - Peter M. Abbott; Joseph R. McConnell; Nathan J. Chellman; Sepp Kipfstuhl; Maria Hörhold; Johannes Freitag; Eliza Cook; William Hutchison; Michael Sigl (Quaternary Science Reviews, 2024)

The distinctive weathering crust habitat of a High Arctic glacier comprises discrete microbial micro‐habitats - Sara M. E. Rassner; Joseph M. Cook; Andrew C. Mitchell; Ian T. Stevens; Tristram D. L. Irvine‐Fynn; Andrew J. Hodson; Arwyn Edwards (Environmental Microbiology, 2024)
Sunlight penetrates the ice surfaces of glaciers and ice sheets, forming a water‐bearing porous ice matrix known as the weathering crust. This crust is home to a significant microbial community. Despite the potential implications of microbial processes in the weathering crust for glacial melting, biogeochemical cycles, and downstream ecosystems, there have been few explorations of its microbial communities. In our study, we used 16S rRNA gene sequencing and shotgun metagenomics of a Svalbard glacier surface catchment to characterise the microbial communities within the weathering crust, their origins and destinies, and the functional potential of the weathering crust metagenome. Our findings reveal that the bacterial community in the weathering crust is distinct from those in upstream and downstream habitats. However, it comprises two separate micro‐habitats, each with different taxa and functional categories. The interstitial porewater is dominated by Polaromonas , influenced by the transfer of snowmelt, and exported via meltwater channels. In contrast, the ice matrix is dominated by Hymenobacter , and its metagenome exhibits a diverse range of functional adaptations. Given that the global weathering crust area and the subsequent release of microbes from it are strongly responsive to climate projections for the rest of the century, our results underscore the pressing need to integrate the microbiome of the weathering crust with other communities and processes in glacial ecosystems.

Spontaneous Behavioural Recovery Following Stroke Relates to the Integrity of Parietal and Temporal Regions - Joseph Y. Nashed; Kaden T. Shearer; Justin Z. Wang; Yining Chen; Elise E. Cook; Allen A. Champagne; Nicole S. Coverdale; Juan Fernandez-Ruiz; Shirley I. Striver; J. Randal Flanagan; Jason P. Gallivan; Douglas J. Cook (Translational Stroke Research, 2024)

Examining the effects of soil entrainment during nuclear cloud rise on fallout predictions using a multiscale atmospheric modeling framework - Katherine A. Lundquist; Robert S. Arthur; Stephanie Neuscamman; Joseph P. Morris; Christian R. Scullard; Andrew W. Cook; Nathan G. Wimer; Peter Goldstein; Gregory D. Spriggs; Lee G. Glascoe; John S. Nasstrom (Journal of Environmental Radioactivity, 2023)

Global variability and controls on the accumulation of fallout radionuclides in cryoconite - Caroline C. Clason; Giovanni Baccolo; Edyta Łokas; Philip N. Owens; Przemyslaw Wachniew; Geoff E. Millward; Alex Taylor; Will H. Blake; Dylan B. Beard; Ewa Poniecka; Nick Selmes; Elizabeth A. Bagshaw; et al. (Science of The Total Environment, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Ancient bears provide insights into Pleistocene ice age refugia in Southeast Alaska - Flavio Augusto da Silva Coelho; Stephanie Gill; Crystal M. Tomlin; Marilena Papavassiliou; Sean D. Farley; Joseph A. Cook; Sarah A. Sonsthagen; George K. Sage; Timothy H. Heaton; Sandra L. Talbot; Charlotte Lindqvist (Molecular Ecology, 2023)
During the Late Pleistocene, major parts of North America were periodically covered by ice sheets. However, there are still questions about whether ice‐free refugia were present in the Alexander Archipelago along the Southeast (SE) Alaska coast during the last glacial maximum (LGM). Numerous subfossils have been recovered from caves in SE Alaska, including American black ( Ursus americanus ) and brown ( U. arctos ) bears, which today are found in the Alexander Archipelago but are genetically distinct from mainland bear populations. Hence, these bear species offer an ideal system to investigate long‐term occupation, potential refugial survival and lineage turnover. Here, we present genetic analyses based on 99 new complete mitochondrial genomes from ancient and modern brown and black bears spanning the last ~45,000 years. Black bears form two SE Alaskan subclades, one preglacial and another postglacial, that diverged >100,000 years ago. All postglacial ancient brown bears are closely related to modern brown bears in the archipelago, while a single preglacial brown bear is found in a distantly related clade. A hiatus in the bear subfossil record around the LGM and the deep split of their pre‐ and postglacial subclades fail to support a hypothesis of continuous occupancy in SE Alaska throughout the LGM for either species. Our results are consistent with an absence of refugia along the SE Alaska coast, but indicate that vegetation quickly expanded after deglaciation, allowing bears to recolonize the area after a short‐lived LGM peak.

Late Cenozoic history and the role of Beringia in assembling a Holarctic cestode species complex - Kurt E. Galbreath; Arseny A. Makarikov; Kayce C. Bell; Stephen E. Greiman; Julie M. Allen; Genevieve M.S. Haas; Chenhong Li; Joseph A. Cook; Eric P. Hoberg (Molecular Phylogenetics and Evolution, 2023)

The coupling of green and brown food webs regulates trophic position in a montane mammal guild - Philip J. Manlick; Joseph A. Cook; Seth D. Newsome (Ecology, 2023)
Food web ecology has revolutionized our understanding of ecological processes, but the drivers of food web properties like trophic position (TP) and food chain length are notoriously enigmatic. In terrestrial ecosystems, above‐ and belowground systems were historically compartmentalized into “green” and “brown” food webs, but the coupling of these systems by animal consumers is increasingly recognized, with potential consequences for trophic structure. We used stable isotope analysis (δ 13 C, δ 15 N) of individual amino acids to trace the flow of essential biomolecules and jointly measure multichannel feeding, food web coupling, and TP in a guild of small mammals. We then tested the hypothesis that brown energy fluxes to aboveground consumers increase terrestrial food chain length via cryptic trophic transfers during microbial decomposition. We found that the average small mammal consumer acquired nearly 70% of their essential amino acids (69.0% ± 7.6%) from brown food webs, leading to significant increases in TP across species and functional groups. Fungi were the primary conduit of brown energy to aboveground consumers, providing nearly half the amino acid budget for small mammals on average (44.3% ± 12.0%). These findings illustrate the tightly coupled nature of green and brown food webs and show that microbially mediated energy flow ultimately regulates food web structure in aboveground consumers. Consequently, we propose that the integration of green and brown energy channels is a cryptic driver of food chain length in terrestrial ecosystems.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Robotic Assessment of Upper Limb Function in a Nonhuman Primate Model of Chronic Stroke - Yining Chen; Meredith C. Poole; Shelby V. Olesovsky; Allen A. Champagne; Kathleen A. Harrison; Joseph Y. Nashed; Nicole S. Coverdale; Stephen H. Scott; Douglas J. Cook (Translational Stroke Research, 2021)

Whole‐genome resequencing reveals persistence of forest‐associated mammals in Late Pleistocene refugia along North America’s North Pacific Coast - Jocelyn P. Colella; Tianying Lan; Sandra L. Talbot; Charlotte Lindqvist; Joseph A. Cook (Journal of Biogeography, 2021)
Aim Numerous glacial refugia have been hypothesized along North America's North Pacific Coast that may have increased divergence of refugial taxa, leading to elevated endemism and subsequently clustered hybrid zones following deglaciation. The locations and community composition of these ice‐free areas remains controversial, but whole‐genome sequences now enable detailed analysis of the demographic and evolutionary histories of refugial taxa. Here, we use genomic data to test spatial and temporal processes of diversification among martens with respect to the Coastal Refugium Hypothesis, to understand the role of climate cycling in shaping diversity across complex landscapes. Location North America and North Pacific Coast archipelagos. Taxon North American martens ( Martes ). Methods Short‐read whole‐genome resequencing data were generated for 11 martens: four M. americana , four M. caurina , two hybrids, and one outgroup ( Martes zibellina ). Sampling was representative of known genetic clades within New World martens, including sampling within insular and continental hybrid zones and along the North Pacific Coast (five island populations). ADMIXTURE , F‐statistics, and D ‐statistics (ABBA‐BABA) were used to identify introgression and infer directionality. Heterozygosity densities, estimated via PSMC, were used to characterize historical demography at and below the species level to infer refugial and colonization processes. Results Forest‐associated Pacific martens ( M. caurina ) are divided into distinct insular and continental clades consistent with the Coastal Refugium Hypothesis. There was no evidence of introgression on islands that received historical translocations of American pine martens ( M. americana ), but introgression was detected in two active zones of secondary contact: one insular and one continental. Only early‐generational hybrids were identified across multiple hybrid zones, a pattern consistent with potential genetic swamping of M. caurina by M. americana . Main conclusions Despite an incomplete fossil record, genomic evidence supports the persistence of forest‐associated martens, likely the insular Pacific marten lineage, along the western edges of the Alexander Archipelago during the Last Glacial Maximum. This discovery informs our understanding of refugial paleoenvironments, critical to interpreting refugial timing, duration, and community composition. Genomic reevaluations of other taxa along North America's North Pacific Coast may yield new and deeper perspectives on the history of refugial forest communities and the role of dynamic climate shifts in shaping high‐latitude diversity across complex insular landscapes.

Conceptual uncertainties in groundwater and porewater fluxes estimated by radon and radium mass balances - Valentí Rodellas; Thomas C. Stieglitz; Joseph J. Tamborski; Pieter van Beek; Aladin Andrisoa; Peter G. Cook (Limnology and Oceanography, 2021)
Radium isotopes and radon are routinely used as tracers to quantify groundwater and porewater fluxes into coastal and freshwater systems. However, uncertainties associated with the determination of the tracer flux are often poorly addressed and often neglect all the potential errors associated with the conceptualization of the system (i.e., conceptual uncertainties). In this study, we assess the magnitude of some of the key uncertainties related to the determination of the radium and radon inputs supplied by groundwater and porewater fluxes into a waterbody (La Palme Lagoon, France). This uncertainty assessment is addressed through a single model ensemble approach, where a tracer mass balance is run multiple times with variable sets of assumptions and approaches for the key parameters determined through a sensitivity test. In particular, conceptual uncertainties linked to tracer concentration, diffusive fluxes, radon evasion to the atmosphere, and change of tracer inventory over time were considered. The magnitude of porewater fluxes is further constrained using a comparison of independent methods: (1) 224 Ra and (2) 222 Rn mass balances in overlying waters, (3) a model of 222 Rn deficit in sediments, and (4) a fluid‐salt numerical transport model. We demonstrate that conceptual uncertainties are commonly a major source of uncertainty on the estimation of groundwater or porewater fluxes and they need to be taken into account when using tracer mass balances. In the absence of a general framework for assessing these uncertainties, this study provides a practical approach to evaluate key uncertainties associated to radon and radium mass balances.

Taxon pulse dynamics, episodic dispersal and host colonization across Beringia drive diversification of a Holarctic tapeworm assemblage - Genevieve M. S. Haas; Eric P. Hoberg; Joseph A. Cook; Heikki Henttonen; Arseny A. Makarikov; Sarah R. Gallagher; Nikolai E. Dokuchaev; Kurt E. Galbreath (Journal of Biogeography, 2020)
Aim We test the predictions of the Stockholm Paradigm, a synthesis of eco‐evolutionary theory explaining the nature of faunal assembly, host range and parasite diversification. Faunal diversification and assembly, manifested in patterns of host colonization, co‐adaptation and parasite speciation, are predicted to emerge as a consequence of alternating episodes of ecological disruption and stability. Specifically, for a diverse cestode genus ( Arostrilepis ), we evaluate the number and direction of Pleistocene dispersal events across Beringia, the number and relative timing of host colonization events and the relationship between host and parasite biogeographic histories and associations through time. Location Beringia and adjacent temperate to arctic biomes in North America and Eurasia. Taxon Arostrilepis (Cyclophyllidea: Hymenolepididae) and its rodent hosts. Methods Multi‐locus phylogenetic reconstruction and biogeographic ancestral range estimation. Results Arostrilepis lineages crossed Beringia eastward into North America a minimum of four times and westward into Asia twice in association with temporally disjunct geographic expansions of three major tribes of cricetid rodents (Arvicolini, Myodini, Lemmini). Inferences of ancestral host associations support at least nine instances of host colonization involving shifts from one rodent tribe or family to another. Several previously unrecognized lineages of Arostrilepis are revealed. Main conclusions Consistent with expectations of the Stockholm Paradigm, episodes of intercontinental dispersal were both frequent in the history of Arostrilepis and preceded a majority of inferred host‐colonization events. Events of historical geographic expansion created numerous opportunities for development of novel host–parasite associations through ecological fitting, as parasites tracked historically conserved resources available across diverse host taxa. Beringia played a major role in shaping rodent/parasite assemblages by mediating dispersal between the northern continents during glacial episodes of the Pleistocene, rather than by serving as a zone of refugial isolation.

We need both natural and energy solutions to stabilize our climate - Bronson W. Griscom; Guy Lomax; Timm Kroeger; Joseph E. Fargione; Justin Adams; Lucy Almond; Deborah Bossio; Susan C. Cook‐Patton; Peter W. Ellis; Christina M. Kennedy; Joseph Kiesecker (Global Change Biology, 2019)

Implications of introgression for wildlife translocations: the case of North American martens - Jocelyn P. Colella; Robert E. Wilson; Sandra L. Talbot; Joseph A. Cook (Conservation Genetics, 2019)

Diversification of deermice (Rodentia: genus Peromyscus ) at their north‐western range limit: genetic consequences of refugial and island isolation - Yadéeh E. Sawyer; Melanie J. Flamme; Thomas S. Jung; Stephen O. MacDonald; Joseph A. Cook (Journal of Biogeography, 2017)
Aim We surveyed the genetic variability of deermice (genus Peromyscus ) at the north‐western edge of their range to test for occupancy in multiple, hypothesized ice‐free regions during the late Pleistocene and explore post‐glacial dynamics. Location North‐western North America. Methods We used sequences from four independent nuclear and mitochondrial loci from 341 specimens of Peromyscus maniculatus, Peromyscus keeni and Peromyscus sp. (Yukon) to assess species limits, population structure, and demographical change as a result of historical climate change, using a Bayesian approach. Species distribution models were built in MaxEnt to explore the niche overlap amongst genetically distinct species. Results Divergence amongst three lineages began before the last interglacial, and each shows signs of post‐glacial expansion. Multilocus species trees strongly support P. keeni and Peromyscus sp. (Yukon) as independent from P. maniculatus . Substantial substructure was observed for P. keeni across the fragmented Alexander Archipelago. Northern lineages or clades ( Peromyscus sp. and P. keeni ) differed in potential ecological distributions. Main conclusions At the extreme north‐western range of deermice in North America, three distinct lineages persist reflecting divergence in at least three ice‐free regions [Beringia, Coastal (near Southeast Alaska) and Southern Continental] throughout the latest Pleistocene glacial cycles. Although spatially proximate in Yukon, no locations were identified where these lineages are in contact. Further, west along the Pacific Coast, P. keeni is widespread across the complex landscape of Southeast Alaska, yet there is limited contemporary gene flow amongst island populations, a finding consistent with the barriers produced by rising sea levels at the end of the Last Glacial Maximum.

Effects of Elevated CO2 on the Swainsonine Chemotypes of Astragalus lentiginosus and Astragalus mollissimus - Daniel Cook; Dale R. Gardner; James A. Pfister; Clinton A. Stonecipher; Joseph G. Robins; Jack A. Morgan (Journal of Chemical Ecology, 2017)

Metabolome‐mediated biocryomorphic evolution promotes carbon fixation in G reenlandic cryoconite holes - Joseph M. Cook; Arwyn Edwards; Mark Bulling; Luis A. J. Mur; Sophie Cook; Jarishma K. Gokul; Karen A. Cameron; Michael Sweet; Tristram D. L. Irvine‐Fynn (Environmental Microbiology, 2016)
Summary Microbial photoautotrophs on glaciers engineer the formation of granular microbial‐mineral aggregates termed cryoconite which accelerate ice melt, creating quasi‐cylindrical pits called ‘cryoconite holes’. These act as biogeochemical reactors on the ice surface and provide habitats for remarkably active and diverse microbiota. Evolution of cryoconite holes towards an equilibrium depth is well known, yet interactions between microbial activity and hole morphology are currently weakly addressed. Here, we experimentally perturbed the depths and diameters of cryoconite holes on the Greenland Ice Sheet. Cryoconite holes responded by sensitively adjusting their shapes in three dimensions (‘biocryomorphic evolution’) thus maintaining favourable conditions for net autotrophy at the hole floors. Non‐targeted metabolomics reveals concomitant shifts in cyclic AMP and fucose metabolism consistent with phototaxis and extracellular polymer synthesis indicating metabolomic‐level granular changes in response to perturbation. We present a conceptual model explaining this process and suggest that it results in remarkably robust net autotrophy on the Greenland Ice Sheet. We also describe observations of cryoconite migrating away from shade, implying a degree of self‐regulation of carbon budgets over mesoscales. Since cryoconite is a microbe‐mineral aggregate, it appears that microbial processes themselves form and maintain stable autotrophic habitats on the surface of the Greenland ice sheet.

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Phylogeography of a Holarctic rodent ( Myodes rutilus ): testing high‐latitude biogeographical hypotheses and the dynamics of range shifts - Brooks A. Kohli; Vadim B. Fedorov; Eric Waltari; Joseph A. Cook (Journal of Biogeography, 2015)
Aim We used the Holarctic northern red‐backed vole ( Myodes rutilus ) as a model organism to improve our understanding of how dynamic, northern high‐latitude environments have affected the genetic diversity, demography and distribution of boreal organisms. We tested spatial and temporal hypotheses derived from previous mitochondrial studies, comparative phylogeography, palaeoecology and the fossil record regarding diversification of M. rutilus in the Palaearctic and Beringia. Location High‐latitude biomes across the Holarctic. Methods We used a multilocus phylogeographical approach combined with species distribution models to characterize the biogeographical and demographic history of M. rutilus . Our molecular assessment included widespread sampling (more than 100 localities), species tree reconstruction and population genetic analyses. Results Three well‐differentiated mitochondrial lineages correspond to geographical regions, but nuclear genes were less structured. Multilocus divergence estimates indicated that diversification of M. rutilus was driven by events occurring before c . 100 ka. Population expansion in all three clades occurred prior to the Last Glacial Maximum ( LGM ) and presumably led to secondary contact. Species distribution modelling predicted a broad LGM distribution consistent with population and range expansion during this period. Main conclusions The biogeographical history of M. rutilus differs from other boreal forest‐associated species. Well‐differentiated clades and the existence of secondary contact zones indicate prolonged isolation and persistence in Eurasian and Beringian refugia. Dynamic demographic and distributional changes emphasize the impact of pre‐ LGM glacial–interglacial cycles on contemporary geographical structure. The Bering Strait was not a significant factor in the diversification of northern red‐backed voles.

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

A multilocus evaluation of ermine ( Mustela erminea ) across the Holarctic, testing hypotheses of Pleistocene diversification in response to climate change - Natalie G. Dawson; Andrew G. Hope; Sandra L. Talbot; Joseph A. Cook (Journal of Biogeography, 2014)
Aim We examined data for ermine ( M ustela erminea ) to test two sets of diversification hypotheses concerning the number and location of late P leistocene refugia, the timing and mode of diversification, and the evolutionary influence of insularization. Location Temperate and sub‐ A rctic N orthern H emisphere. Methods We used up to two mitochondrial and four nuclear loci from 237 specimens for statistical phylogeographical and demographic analyses. Coalescent species‐tree estimation used a Bayesian approach for clade divergence based on external mutation rate calibrations. Approximate Bayesian methods were used to assess population size, timing of divergence and gene flow. Results Limited structure coupled with evidence of population growth across broad regions, including previously ice‐covered areas, indicated expansion from multiple centres of differentiation, but high endemism along the N orth P acific coast ( NPC ). A bifurcating model of diversification with recent growth spanning three glacial cycles best explained the empirical data. Main conclusions A newly identified clade in N orth A merica indicated a fourth refugial area for ermine. The shallow coalescence of all extant ermine reflects a recent history of diversification overlying a deeper fossil record. Post‐glacial colonization has led to potential contact zones for multiple lineages in north‐western N orth A merica. A model of diversification of ermine accompanied by recent gene flow was marginally less well supported than a model of divergence of major clades in response to the most recent glacial cycles.

Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2014)
HIV-associated neurocognitive disorder (HAND), characterized by a wide spectrum of behavioral, cognitive, and motor dysfunctions, continues to affect approximately 50 % of HIV(+) patients despite the success of combination antiretroviral drug therapy (cART) in the periphery. Of note, potential toxicity of antiretroviral drugs in the central nervous system (CNS) remains remarkably underexplored and may contribute to the persistence of HAND in the cART era. Previous studies have shown antiretrovirals (ARVs) to be neurotoxic in the peripheral nervous system in vivo and in peripheral neurons in vitro. Alterations in lipid and protein metabolism, mitochondrial damage, and oxidative stress all play a role in peripheral ARV neurotoxicity. We hypothesized that ARVs also induce cellular stresses in the CNS, ultimately leading to neuronal damage and contributing to the changing clinical and pathological picture seen in HIV-positive patients in the cART era. In this report, we show that ARVs are neurotoxic in the CNS in both pigtail macaques and rats in vivo. Furthermore, in vitro, ARVs lead to accumulation of reactive oxygen species (ROS), and ultimately induction of neuronal damage and death. Whereas ARVs alone caused some activation of the endogenous antioxidant response in vitro, augmentation of this response by a fumaric acid ester, monomethyl fumarate (MMF), blocked ARV-induced ROS generation, and neuronal damage/death. These findings implicate oxidative stress as a contributor to the underlying mechanisms of ARV-induced neurotoxicity and will provide an access point for adjunctive therapies to complement ARV therapy and reduce neurotoxicity in this patient population.

Using biogeographical history to inform conservation: the case of P reble's meadow jumping mouse - Jason L. Malaney; Joseph A. Cook (Molecular Ecology, 2013)
The last P leistocene deglaciation shaped temperate and boreal communities in N orth A merica. Rapid northward expansion into high latitudes created distinctive spatial genetic patterns within species that include closely related groups of populations that are now widely spread across latitudes, while longitudinally adjacent populations, especially those near the southern periphery, often are distinctive due to long‐term disjunction. Across a spatial expanse that includes both recently colonized and long‐occupied regions, we analysed molecular variation in zapodid rodents to explore how past climate shifts influenced diversification in this group. By combining molecular analyses with species distribution modelling and tests of ecological interchangeability, we show that the lineage including the P reble's meadow jumping mouse ( Z apus hudsonius preblei ), a US federally listed taxon of conservation concern, is not restricted to the southern R ocky M ountains. Rather, populations along the F ront Range are part of a single lineage that is ecologically indistinct and extends to the far north. Of the 21 lineages identified, this N orthern lineage has the largest geographical range and low measures of intralineage genetic differentiation, consistent with recent northward expansion. Comprehensive sampling combined with coalescent‐based analyses and niche modelling leads to a radically different view of geographical structure within jumping mice and indicates the need to re‐evaluate their taxonomy and management. This analysis highlights a premise in conservation biology that biogeographical history should play a central role in establishing conservation priorities.

Temporal, spatial and ecological dynamics of speciation among amphi‐ B eringian small mammals - Andrew G. Hope; Naoki Takebayashi; Kurt E. Galbreath; Sandra L. Talbot; Joseph A. Cook (Journal of Biogeography, 2013)
Aim Quaternary climate cycles played an important role in promoting diversification across the N orthern H emisphere, although details of the mechanisms driving evolutionary change are still poorly resolved. In a comparative phylogeographical framework, we investigate temporal, spatial and ecological components of evolution within a suite of H olarctic small mammals. We test a hypothesis of simultaneous divergence among multiple taxon pairs, investigating time to coalescence and demographic change for each taxon in response to a combination of climate and geography. Location Beringia, the nexus of the northern continents. Methods We used approximate B ayesian computation methods to test for simultaneous divergence among eight pairs of taxa, using cytochrome b gene sequences. We calculated coalescence times for eastern and western components of each pair and for the combined pairs, and relate dates to Q uaternary climatic periodicity and combinations of environmental events and physical barriers. Population growth and expansion statistics were used to test evolutionary responses among taxa, including range shifts, persistence or periodic extirpation. Species distribution models ( SDM s) for each taxon were used to predict their geographical ranges during the present interglacial, L ast G lacial M aximum and previous interglacial. Results Multiple divergence events across B eringia were primarily coincident with extreme glacial cycles of the late Q uaternary. Structure within B eringia is spatially consistent with at least three environmental barriers arising at different times: the K olyma U plands, B ering S trait and portions of the B ering I sthmus. Levels of divergence varied substantially, indicating evolutionary processes spanning deep and shallow time‐scales. The different demographics among taxa reflect their distinct ecological responses. SDM s predicted regional distributional changes through time and different spatial responses among taxa. Main conclusions Beringia predominantly constituted a dispersal corridor during the early Q uaternary and a major centre of endemism in the late Q uaternary. Coincident with severe glacial cycles, small mammal species were ‘caught’ in B eringia and diversified over multiple climatic phases. Relative genetic differentiation across B eringia appears to be related to ecological differences reflecting a gradual adaptation to B eringian environments through time. Some methodological constraints associated with resolving recent (late Q uaternary) isolation events or drawing inferences from a single locus are discussed.

Sea level, topography and island diversity: phylogeography of the P uerto R ican Red‐eyed C oquí, E leutherodactylus antillensis - Brittany S. Barker; Javier A. Rodríguez‐Robles; Vani S. Aran; Ashley Montoya; Robert B. Waide; Joseph A. Cook (Molecular Ecology, 2012)
Quaternary climatic oscillations caused changes in sea level that altered the size, number and degree of isolation of islands, particularly in land‐bridge archipelagoes. Elucidating the demographic effects of these oscillations increases our understanding of the role of climate change in shaping evolutionary processes in archipelagoes. The P uerto R ican B ank ( PRB ) ( P uerto R ico and the E astern I slands, which comprise V ieques, C ulebra, the V irgin I slands and associated islets) in the eastern C aribbean S ea periodically coalesced during glaciations and fragmented during interglacial periods of the quaternary. To explore population‐level consequences of sea level changes, we studied the phylogeography of the frog E leutherodactylus antillensis across the archipelago. We tested hypotheses encompassing vicariance and dispersal narratives by sequencing mt DNA ( c . 552 bp) of 285 individuals from 58 localities, and four nu DNA introns (totalling c . 1633 bp) from 173 of these individuals. We found low support for a hypothesis of divergence of the E astern I slands populations prior to the start of the penultimate interglacial c . 250 kya, and higher support for a hypothesis of colonization of the E astern I slands from sources in eastern P uerto R ico during the penultimate and last glacial period, when a land bridge united the PRB . The R ío G rande de L oíza B asin in eastern P uerto R ico delineates a phylogeographic break. Haplotypes shared between the PRB and S t. C roix (an island c . 105 km south‐east of this archipelago) likely represent human‐mediated introductions. Our findings illustrate how varying degrees of connectivity and isolation influence the evolution of tropical island organisms.

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Biogeography of the Australian monsoon tropics - D. M. J. S. Bowman; G. K. Brown; M. F. Braby; J. R. Brown; L. G. Cook; M. D. Crisp; F. Ford; S. Haberle; J. Hughes; Y. Isagi; L. Joseph; J. McBride; et al. (Journal of Biogeography, 2010)
Aim This paper reviews the biogeography of the Australian monsoon tropical biome to highlight general patterns in the distribution of a range of organisms and their environmental correlates and evolutionary history, as well as to identify knowledge gaps. Location Northern Australia, Australian Monsoon Tropics (AMT). The AMT is defined by areas that receive more than 85% of rainfall between November and April. Methods Literature is summarized, including the origin of the monsoon climate, present‐day environment, biota and habitat types, and phylogenetic and geographical relationships of selected organisms. Results Some species are widespread throughout the AMT while others are narrow‐range endemics. Such contrasting distributions correspond to present‐day climates, hydrologies (particularly floodplains), geological features (such as sandstone plateaux), fire regimes, and vegetation types (ranging from rain forest to savanna). Biogeographical and phylogenetic studies of terrestrial plants (e.g. eucalypts) and animals (vertebrates and invertebrates) suggest that distinct bioregions within the AMT reflect the aggregated effects of landscape and environmental history, although more research is required to determine and refine the boundaries of biogeographical zones within the AMT. Phylogenetic analyses of aquatic organisms (fishes and prawns) suggest histories of associations with drainage systems, dispersal barriers, links to New Guinea, and the existence of Lake Carpentaria, now submerged by the Gulf of Carpentaria. Complex adaptations to the landscape and climate in the AMT are illustrated by a number of species. Main conclusions The Australian monsoon is a component of a single global climate system, characterized by a dominant equator‐spanning Hadley cell. Evidence of hot, seasonally moist climates dates back to the Late Eocene, implying that certain endemic elements of the AMT biota have a long history. Vicariant differentiation is inferred to have separated the Kimberley and Arnhem Land bioregions from Cape York Peninsula/northern Queensland. Such older patterns are overlaid by younger events, including dispersal from Southeast Asia, and range expansions and contractions. Future palaeoecological and phylogenetic investigations will illuminate the evolution of the AMT biome. Understanding the biogeography of the AMT is essential to provide a framework for ecological studies and the sustainable development of the region.

Effects of global irrigation on the near-surface climate - William J. Sacks; Benjamin I. Cook; Nikolaus Buenning; Samuel Levis; Joseph H. Helkowski (Climate Dynamics, 2009)

Effects of Increasing Urbanization on the Ecological Integrity of Open Space Preserves - Hayriye Esbah; Edward A. Cook; Joseph Ewan (Environmental Management, 2009)

Five thousand years of sediment transfer in a high arctic watershed recorded in annually laminated sediments from Lower Murray Lake, Ellesmere Island, Nunavut, Canada - Timothy L. Cook; Raymond S. Bradley; Joseph S. Stoner; Pierre Francus (Journal of Paleolimnology, 2009)

Nicotine effects on affective response in depression-prone smokers - Bonnie Spring; Jessica Werth Cook; Bradley Appelhans; Anne Maloney; Malia Richmond; Jocelyn Vaughn; Joseph Vanderveen; Donald Hedeker (Psychopharmacology, 2008)

Eastward Ho: phylogeographical perspectives on colonization of hosts and parasites across the Beringian nexus - Eric Waltari; Eric P. Hoberg; Enrique P. Lessa; Joseph A. Cook (Journal of Biogeography, 2007)
The response of Arctic organisms and their parasites to dramatic fluctuations in climate during the Pleistocene has direct implications for predicting the impact of current climate change in the North. An increasing number of phylogeographical studies in the Arctic have laid a framework for testing hypotheses concerning the impact of shifting environmental conditions on transcontinental movement. We review 35 phylogeographical studies of trans‐Beringian terrestrial and freshwater taxa, both hosts and parasites, to identify generalized patterns regarding the number, direction and timing of trans‐continental colonizations. We found that colonization across Beringia was primarily from Asia to North America, with many events occurring in the Quaternary period. The 35 molecular studies of trans‐Beringian organisms we examined focused primarily on the role of glacial cycles and refugia in promoting diversification. We address the value of establishing testable hypotheses related to high‐latitude biogeography. We then discuss future prospects in Beringia related to coalescent theory, palaeoecology, ancient DNA and synthetic studies of arctic host–parasite assemblages highlighting their cryptic diversity, biogeography and response to climate variation.

Temporal resolution of the Florida manatee (Trichechus manatus latirostris) auditory system - David A. Mann; Debborah E. Colbert; Joseph C. Gaspard; Brandon M. Casper; Mandy L. H. Cook; Roger L. Reep; Gordon B. Bauer (Journal of Comparative Physiology A, 2005)

Hares on ice: phylogeography and historical demographics of Lepus arcticus , L. othus , and L. timidus (Mammalia: Lagomorpha) - ERIC WALTARI; JOSEPH A. COOK (Molecular Ecology, 2005)
Phylogeographical investigations of arctic organisms provide spatial and temporal frameworks for interpreting the role of climate change on biotic diversity in high‐latitude ecosystems. Phylogenetic analyses were conducted on 473 base pairs of the mitochondrial control region in 192 arctic hares ( Lepus arcticus , Lepus othus , Lepus timidus ) and two individual Lepus townsendii . The three arctic hare species are closely related. All L. othus individuals form one well‐supported clade, L. arcticus individuals form two well‐supported clades, and L. timidus individuals are scattered throughout the phylogeny. Arctic hare distribution was altered dramatically following post‐Pleistocene recession of continental ice sheets. We tested for genetic signatures of population expansion for hare populations now found in deglaciated areas. Historical demographic estimates for 12 arctic hare populations from throughout their range indicate that L. arcticus and L. othus persisted in two separate North American arctic refugia (Beringia and High Canadian Arctic) during glacial advances of the Pleistocene, while the high genetic diversity in L. timidus likely reflects multiple Eurasian refugia.

Postglacial expansion of the southern red‐backed vole ( Clethrionomys gapperi ) in North America - AMY M. RUNCK; JOSEPH A. COOK (Molecular Ecology, 2005)
Dynamic climatic oscillations of the Pleistocene dramatically changed the distributions of high latitude species. Molecular investigations of a variety of organisms show that processes of postglacial colonization of boreal regions were more complex than initially thought. Phylogeographical and coalescent analyses were conducted on partial sequences of the cytochrome b gene (600 bp) from 64 individuals of Clethrionomys gapperi from North Carolina, Pennsylvania, Minnesota, Idaho, Washington, British Columbia, Northwest Territories, and Alaska to test hypotheses relating to Pleistocene refugia and postglacial colonization routes. Three divergent clades (east, west, central) were identified with highest net divergence ( d A = 5.2%) between the eastern and western clades. Populations from the recently deglaciated higher latitudes of Canada and Alaska are closely related to lower latitude populations of the central clade ( d A = 1.2%) suggesting recent expansion from this midwestern region. No representatives from the east or west clade were found at latitudes higher than 50°N, indicating that postglacial colonization occurred through a midcontinental route. The high latitude population from the Northwest Territories exhibited demographic patterns and genetic diversity consistent with a stable noncolonizing population. This population is found near the Mackenzie range, where the two continental ice sheets were believed to have coalesced. Molecular variation observed in this population may be the result of leading edge population diversifying in the continental corridor or may reflect the signal of a high latitude refugial population.

A Signal for Independent Coastal and Continental histories among North American wolves - BYRON V. WECKWORTH; SANDRA TALBOT; GEORGE K. SAGE; DAVID K. PERSON; JOSEPH COOK (Molecular Ecology, 2005)
Relatively little genetic variation has been uncovered in surveys across North American wolf populations. Pacific Northwest coastal wolves, in particular, have never been analysed. With an emphasis on coastal Alaska wolf populations, variation at 11 microsatellite loci was assessed. Coastal wolf populations were distinctive from continental wolves and high levels of diversity were found within this isolated and relatively small geographical region. Significant genetic structure within southeast Alaska relative to other populations in the Pacific Northwest, and lack of significant correlation between genetic and geographical distances suggest that differentiation of southeast Alaska wolves may be caused by barriers to gene flow, rather than isolation by distance. Morphological research also suggests that coastal wolves differ from continental populations. A series of studies of other mammals in the region also has uncovered distinctive evolutionary histories and high levels of endemism along the Pacific coast. Divergence of these coastal wolves is consistent with the unique phylogeographical history of the biota of this region and re‐emphasizes the need for continued exploration of this biota to lay a framework for thoughtful management of southeast Alaska.

Benzodiazepines and heightened aggressive behavior in rats: reduction by GABAA/?1 receptor antagonists - Shannon L. Gourley; Joseph F. DeBold; Wenyuan Yin; James Cook; Klaus A. Miczek (Psychopharmacology, 2005)

Genetic consequences of Pleistocene glaciations for the tundra vole ( Microtus oeconomus ) in Beringia - Kurt E. Galbreath; Joseph A. Cook (Molecular Ecology, 2004)
Repeated glacial events during the Pleistocene fragmented and displaced populations throughout the northern continents. Different models of the effects of these climate‐driven events predict distinct phylogeographic and population genetic outcomes for high‐latitude faunas. The role of glaciations in (i) promoting intraspecific genetic differentiation and (ii) influencing genetic diversity was tested within a phylogeographic framework using the rodent Microtus oeconomus . The spatial focus for the study was Beringia, which spans eastern Siberia and northwestern North America, and was a continental crossroads and potential high arctic refugium during glaciations. Variation in mitochondrial DNA (cytochrome b and control region; 214 individuals) and nuclear DNA (ALDH1 intron; 63 individuals) was investigated across the Beringian region. Close genetic relationships among populations on either side of the Bering Strait are consistent with a history of periodic land connections between North America and Asia. A genetic discontinuity observed in western Beringia between members of a Central Asian clade and a Beringian clade is geographically congruent with glacial advances and with phylogeographic discontinuities identified in other organisms. Divergent island populations in southern Alaska were probably initially isolated by glacial vicariance, but subsequent differentiation has resulted from insularity. Tests of the genetic effects of postglacial colonization were largely consistent with expansion accompanied by founder effect bottlenecking, which yields reduced diversity in populations from recently deglaciated areas. Evidence that populations in the Beringian clade share a history of expansion from a low‐diversity ancestral population suggests that Beringia was colonized by a small founder population from central Asia, which subsequently expanded in isolation.

American marten ( Martes americana ) in the Pacific Northwest: population differentiation across a landscape fragmented in time and space - Maureen P. Small; Karen D. Stone; Joseph A. Cook (Molecular Ecology, 2003)
American marten ( Martes americana ) have a close association with mature temperate forests, a habitat that expanded throughout the Pacific Northwest as glaciers receded at the end of the Pleistocene. Similar to several other forest‐associated mammals in North America (e.g. black bear), genetic analysis of the marten shows a deep phylogeographical subdivision that reflects populations with distinctive evolutionary histories. Using a suite of 14 microsatellite markers, we explored the genetic structure of marten populations in two reciprocally monophyletic clades in the Pacific Northwest identified previously as M. caurina and M. americana by mitochondrial haplotypes and morphology. Microsatellite phylogeographical patterns were congruent with mitochondrial analyses. These independent data sets shed light upon hybridization patterns, population structure and evolutionary histories. Hybridization between M. caurina and M. americana individuals was documented in two regions of sympatry (Kuiu Island in southeastern Alaska and southern Montana). Northern insular populations of M. caurina exhibited higher differentiation and lower variability relative to northern populations of M. americana . Greater divergence among M. caurina populations may reflect longer isolation and persistence in coastal forest habitat that was fragmented by rising sea level in the early Holocene. Lower differentiation among northern M. americana populations and close relationship to other continental M. americana populations may reflect more recent expansion into the Pacific Northwest and/or continued gene flow among populations. Differentiation among M. caurina populations was attributed to habitat fragmentation (i.e. rising sea level), as opposed to isolation‐by‐distance; oceanic straits pose significant barriers to gene flow among M. caurina populations and between populations of M. caurina and M. americana .

Post‐glacial colonization of northwestern North America by the forest‐associated American marten ( Martes americana , Mammalia: Carnivora: Mustelidae) - Karen D. Stone; Rodney W. Flynn; Joseph A. Cook (Molecular Ecology, 2002)
Phylogeographic patterns were used to assess intraspecific diversification of American martens ( Martes americana ). Within martens, two morphological groups ( americana and caurina ) have been recognized, though the level of distinction between them has been debated. We examined mitochondrial cytochrome b gene haplotypes from 680 martens to explore the colonization history of the Pacific Northwest and found two clades that correspond to the morphological groups. The widespread americana clade extends from interior Alaska south to Montana and eastward to Newfoundland and New England (i.e. northwestern, north‐central and northeastern North America). The caurina clade occurs in western North America, minimally extending from Admiralty Island (southeastern Alaska) south to Oregon and Wyoming. Our data indicated two colonization events for the Pacific Northwest (one by members of each clade) and were consistent with the persistence of populations throughout past glacial periods in eastern and western refugia. Due to vegetational and geological history following the past deglaciation, we hypothesize that martens of the caurina clade spread along the North Pacific Coast, and into southeastern Alaska, earlier than martens of the americana clade. Mismatch distributions for the americana clade were indicative of populations that recently experienced demographic expansion, while mismatch distributions for the caurina clade suggested that populations were at equilibrium. These clades are reciprocally monophyletic and distinctive (interclade divergence ranged from 2.5 to 3.0% (uncorrected p ), whereas, intraclade divergence was

A nuclear perspective on endemism in northern flying squirrels (Glaucomys sabrinus) of the Alexander Archipelago, Alaska - Allison L. Bidlack; Joseph A. Cook (Conservation Genetics, 2002)

Phylogeography of endemic ermine ( Mustela erminea ) in southeast Alaska - Melissa A. Fleming; Joseph A. Cook (Molecular Ecology, 2002)
The North Pacific Coast (NPC) of North America is a region of high mammalian endemism, possibly due to its highly fragmented landscape and complex glacial history. For example, four island and one mainland subspecies of ermine, Mustela erminea , have been described as endemic to southeast Alaska alone. To better understand the role of past climatic change in generating diversity in the region, we examined DNA sequence variation in the mitochondrial cytochrome b gene of 210 ermine from across North America, with an emphasis on Alaska and British Columbia. We found three distinct (1.5–3.6% uncorrected ‘p’) lineages of ermine, all of which occur in southeast Alaska. One lineage includes a southeast Alaska endemic and specimens from Alaska (outside of southeast) and Eurasia. A second lineage includes two southeast Alaskan endemics and ermine from western Canada and the coterminous United States. The close relationships of these purported endemics to ermine outside of southeast Alaska suggest that they colonized the region from Beringian and southern glacial refugia, respectively, following deglaciation of the NPC. The third lineage appears restricted to the Prince of Wales Island complex in southeast Alaska (two subspecies) and Graham Island (Haida Gwaii), British Columbia. This restricted distribution suggests that these populations may be derived from relicts that persisted in a coastal refugium during the Wisconsin glaciation. Studies of nuclear genes and adaptive morphological evolution are necessary to further explore discrepancies between the geographical pattern of differentiation based on mtDNA and the existing subspecific taxonomy based on morphology.

Phylogeography of the dusky shrew, Sorex monticolus (Insectivora, Soricidae): insight into deep and shallow history in northwestern North America - John R. Demboski; Joseph A. Cook (Molecular Ecology, 2001)
Phylogenetic relationships among the dusky shrew ( Sorex monticolus ) and eight related species ( S . bairdi , S . bendirii , S . neomexicanus , S. ornatus , S . pacificus , S . palustris , S . sonomae and S. vagrans ) were assessed using sequences from the mitochondrial cytochrome b gene (801 bp). Analyses using parsimony and maximum likelihood revealed significant molecular variation not reflected in previous morphological studies of these species. Conversely, three morphologically defined species ( S. bairdi , S. neomexicanus and S. pacificus ) were poorly differentiated. Sorex ornatus and S. vagrans represented basal taxa for a more inclusive group that included: (i) a widespread Continental clade containing S. monticolus (Arizona to Alaska, including S . neomexicanus ); (ii) a Coastal clade containing S. monticolus (Oregon to south‐east Alaska, including S . bairdi and S . pacificus ); (iii) the semiaquatic species ( S. bendirii and S . palustris ); and (iv) S. sonomae . Additional subdivision was observed within the Continental clade corresponding to populations from the northern and southern Rocky Mountains. Average uncorrected sequence divergence between the Coastal and Continental clades was 5.3% (range 4.5–6.2%), which exceeds many interspecific comparisons within this species complex and within the genus Sorex . Lack of resolution of internal nodes within topologies suggests a deep history of rapid diversification within this group. Late Pleistocene/Holocene glacial perturbations are reflected in the shallow phylogeographic structure within these clades in western North America. Our results suggest also that S. monticolus is not monophyletic under current taxonomic nomenclature. This perspective on phylogeographic history was developed within a growing comparative framework for other organisms in western North America.

Sex-related differences in the antinociceptive effects of opioids: importance of rat genotype, nociceptive stimulus intensity, and efficacy at the µ opioid receptor - Charles D. Cook; Andrew C. Barrett; Emily L. Roach; Joseph R. Bowman; Mitchell J. Picker (Psychopharmacology, 2000)

MtDNA Evidence for Repeated Pulses of Speciation Within Arvicoline and Murid Rodents - Chris J. Conroy; Joseph A. Cook (Journal of Mammalian Evolution, 1999)

Microsatellite markers for American mink ( Mustela vison ) and ermine ( Mustela erminea ) - Melissa A. Fleming; Elaine A. Ostrander; Joseph A. Cook (Molecular Ecology, 1999)

Molecular Phylogeny of Tuco-Tucos, Genus Ctenomys (Rodentia: Octodontidae): Evaluation of the mendocinus Species Group and the Evolution of Asymmetric Sperm - Guillermo D'Elía; Enrique P. Lessa; Joseph A. Cook (Journal of Mammalian Evolution, 1999)

Mammalian biogeography of the Alexander Archipelago of Alaska: a north temperate nested fauna - Chris J. Conroy; John R. Demboski; Joseph A. Cook (Journal of Biogeography, 1999)
Summary Aim A large number of studies have analysed the distribution of mammals within archipelagos, yet few have focused on islands that were heavily glaciated and subsequently colonized following deglaciation. Location We explored the relative effects of island area and isolation on faunal composition based on twenty‐three mammalian taxa of twenty‐four islands of the Alexander Archipelago, Southeast Alaska. Methods We used regression of log‐transformed variables and several indices of nestedness. Results These faunas showed significant nested structure using tests of nestedness and regression models. Unlike most landbridge and mainland archipelagos studied previously, isolation appears to be the primary factor determining patterns of species richness. Main conclusions Colonization ability of particular taxa, rather than extinction, has determined this nested structure. We suggest that other higher latitude archipelagos may show similar historical patterns.